Ways to live forever - Nicholls, Sally, 1983- (New York : Scholastic, 2011)
Eleven-year-old Sam McQueen, who has leukemia, writes a book during the last three months of his life, in which he tells about what he would like to accomplish, how he feels, and things that have happened to him.
Includes bibliographical references (p. 211-212).
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
Booklist, November 2008.
Bulletin (Center for Children's books), November 2008.
Keywords: Authorship -- Juvenile fiction; Death -- Juvenile fiction; Families -- Juvenile fiction; Leukemia -- Juvenile fiction; Authorship -- Fiction; Death -- Fiction; Family life -- Fiction; Leukemia -- Fiction; Authorship -- Fiction; Death -- Fiction; Family life -- Fiction; Leukemia -- Fiction